2008
DOI: 10.1124/mol.107.042663
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TRPA1 by Farnesyl Thiosalicylic Acid

Abstract: The nonselective cation channel TRPA1 (ANKTM1, p120) is a potential mediator of pain, and selective pharmacological modulation of this channel may be analgesic. Although several TRPA1 activators exist, these tend to be either reactive or of low potency and/or selectivity. The aim of the present study, therefore, was to identify novel TRPA1 agonists. Using a combination of calcium fluorescent assays and whole-cell electrophysiology, we discovered several compounds that possess potent, selective TRPA1-activating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…To confirm the TRPA1 agonistic activity of pinacidil by a relatively direct approach, we used the whole-cell patch clamp technique. It has been reported that TRPA1 is often desensitized in the presence of extracellular Ca 2+ [10,30]. It has even been reported that calcium ions alone can directly gate heterologously expressed TRPA1 [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the TRPA1 agonistic activity of pinacidil by a relatively direct approach, we used the whole-cell patch clamp technique. It has been reported that TRPA1 is often desensitized in the presence of extracellular Ca 2+ [10,30]. It has even been reported that calcium ions alone can directly gate heterologously expressed TRPA1 [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…3) AITC content of wasabi is known to be about 100-150 mg per 100 g. 3,4) The intake of pungent components enhances sympathetic nervous activities and energy metabolism. 1,[6][7][8][9][10] In general, transient receptor potential (TRP) cation channels are deeply related to these mechanisms. 4) Especially, TRP ankyrin 1 (TRPA1) has a central role in the pain response to endogeneous inflammatory mediators and volatile irritant, including AITC (wasabi), cinnamaldehyde (cinnamon) and allicin (garlic).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Many studies showed that TRPA1 was expressed on the protein level in several gastrointestinal mucosa of small intestine, colon and duodenal mucosa. [6][7][8][9][10] Although pungent components have been known to enhance energy consumption, there is very little information about AITC. Recent study showed that AITC induced adrenaline secretion via activation of the sensory nerves expressing TRPA1 and adrenal sympathetic nerves in rats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations